The TRANSCOMP Dataset of Literary Translations from 120 Languages and a Parallel Collection of English-language Originals. (26th December 2022) - Erlin, Matt; Piper, Andrew; Knox, Douglas; Pentecost, Stephen; Blank, Allie
The TRANSCOMP Dataset of Literary Translations is a collection of document-level word frequencies sampled from 10, 631 translations into English of global literary fiction published since 1950, together with a historically matched parallel corpus of 10, 682 fictional works originally published in English. We provide CSV files with word frequency counts for 10, 000-word samples taken from each text. The associated metadata is available in a separate CSV. These data will be useful to literary scholars and linguists working in translation studies, and those interested in the linguistic, stylistic, and thematic specificity of translations from particular regions.